2018
DOI: 10.1103/physrevd.97.072013
|View full text |Cite
|
Sign up to set email alerts
|

Test of lepton flavor universality by the measurement of the B0D*τ+ντ branching fraction using three-prong et al.

Abstract: Test of lepton flavor universality by the measurement of the B 0 → D Ã − τ + ν τ branching fraction using three-prong τ decays R. Aaij et al.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
295
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 341 publications
(305 citation statements)
references
References 52 publications
9
295
1
Order By: Relevance
“…The SM calculations for these ratios, performed by several groups [5][6][7][8], are averaged by HFLAV [9] to obtain R(D) = 0.299 ± 0.003 and R(D * ) = 0.258 ± 0.005. Semitauonic B decays were first observed by Belle in 2007 [10], with subsequent studies reported by Belle [11][12][13][14], BaBar [15], and LHCb [16,17]. The average values of the experimental results, excluding the result presented in this Letter, are R(D) = 0.407 ± 0.039 ± 0.024 and R(D * ) = 0.306 ± 0.013 ± 0.007 [9], where the first uncertainty is statistical and the second is systematic.…”
mentioning
confidence: 86%
“…The SM calculations for these ratios, performed by several groups [5][6][7][8], are averaged by HFLAV [9] to obtain R(D) = 0.299 ± 0.003 and R(D * ) = 0.258 ± 0.005. Semitauonic B decays were first observed by Belle in 2007 [10], with subsequent studies reported by Belle [11][12][13][14], BaBar [15], and LHCb [16,17]. The average values of the experimental results, excluding the result presented in this Letter, are R(D) = 0.407 ± 0.039 ± 0.024 and R(D * ) = 0.306 ± 0.013 ± 0.007 [9], where the first uncertainty is statistical and the second is systematic.…”
mentioning
confidence: 86%
“…Σ cos ∆φ ≡ cos(∆φ( , / E T )) + cos(∆φ(τ had , / E T )), (15) discriminates against background events containing leptonically decaying W bosons. Here ∆φ( , / E T ) is the azimuthal angle between the and the / E T and ∆φ(τ had , / E T ) is the azimuthal angle between the τ had and the / E T .…”
Section: Tt Candidate Event Selection Criteriamentioning
confidence: 99%
“…Systematic uncertainties due to hadronic effects largely cancel in these ratios. A combination [5] of the results from the BaBar [6,7], Belle [8,9,10,11,12], and LHCb [13, 14,15] experiments yields the results:…”
Section: Introductionmentioning
confidence: 99%
“…In our proposed approach, we use the fact that the momentum of the partially reconstructed B 0 s meson can be determined from the position of its decay vertex, assuming that the mass of the invisible state is known. Similar topological reconstruction has been used in studies of semileptonic decays at LHCb [9]. With the correctly determined B 0 s momentum, the decay time distribution will exhibit oscillations with a known frequency.…”
Section: Introductionmentioning
confidence: 97%